Effects of two different low-volume resistance training programs applied during the off-season period on the speed-power performance of elite youth soccer players - Loturco, I.; Nunes, R. F. H.; Lampert, R. R.; Silva, R. L. P.; Hespanhol, J. E.; Novack, L. F.; Conde, J. H. S.; Pereira, L. A.; McGuigan, M. R. (The Journal of Strength and Conditioning Research, 2024)
The aim of this study was to analyze the changes in the speed-power performance of elite youth soccer players submitted to 2 different low-volume resistance training programs during the off-season period. Twenty under-17 players were randomly allocated to "traditional nonballistic" or "ballistic training" groups. Countermovement jump (CMJ), 20-m sprinting speed, and half-squat (HS) power tests were performed after the final match of the season (pretesting session) and at the beginning of the subsequent season (post-testing session), after 4 weeks of detraining. Between-group differences were assessed using a 2-way ANOVA with repeated measures followed by the Tukey's post hoc test. Performance variations were individually analyzed with the use of the "true changes" calculation. At post-tests, CMJ height and HS power remained unchanged (p > 0.05) but similar and significant improvements in sprint speed were observed in both groups (p < 0.05). However, notably, a larger number of players in the ballistic group exhibited "true changes" in HS power (i.e., 55 vs. 33%, compared with the traditional group, respectively). In conclusion, either low-volume ballistic or traditional resistance training schemes were able to increase sprint speed and maintain power output during a short interseason break in youth soccer players. Despite this apparent similarity, at the individual level, ballistic movements were more efficient at improving lower-body power. Practitioners can use the strategies described here to improve the sprint and power performance of soccer players during short periods of soccer-specific training cessation.